2015
DOI: 10.1089/bfm.2015.0008
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor in Sera of Breastfed Epileptic Infants and in Breastmilk of Their Mothers

Abstract: Serum and milk BDNF levels are higher in epileptic infants than in controls and may be used as a marker of disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
0
17
1
Order By: Relevance
“…Using an assay validated for human milk, we found that BDNF was not detectable in any of our samples, which is inconsistent with the findings of others who used the same commercial ELISA [23,25]. Li et al measured BDNF in the breast milk of 42 healthy Chinese women at 3, 10, and 30 days postpartum and reported average BDNF levels of 10-13 pg/mL, which is below the standard curve range of 15.6-1000 pg/mL [23].…”
Section: Brain Derived Neurotrophic Factorcontrasting
confidence: 99%
See 3 more Smart Citations
“…Using an assay validated for human milk, we found that BDNF was not detectable in any of our samples, which is inconsistent with the findings of others who used the same commercial ELISA [23,25]. Li et al measured BDNF in the breast milk of 42 healthy Chinese women at 3, 10, and 30 days postpartum and reported average BDNF levels of 10-13 pg/mL, which is below the standard curve range of 15.6-1000 pg/mL [23].…”
Section: Brain Derived Neurotrophic Factorcontrasting
confidence: 99%
“…Total BDNF was measured in duplicate using a Quantikine Total BDNF ELISA kit (part number DBNT00, R&D Systems, Minneapolis, MN) which has a standard curve range of 15.6-1000 pg/mL. This method was selected because it was used in two of the three published studies on BDNF in human milk, and was the only published methods available at the time that had been validated by the manufacturer for use with human milk [23,25]. Samples were prepared according to the manufacturer's instructions to centrifuge for 15 min at 1000 RPM, remove the aqueous fraction, and repeat two more times.…”
Section: Milk Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, breast milk contains brain-derived neurotrophic factor (BDNF) and lactoferrin. BDNF is a vital trophic protein for development and maintenance of the nervous system and essential to molecular mechanisms of synaptic plasticity (11,12) . In experimental models it has been shown that lactoferrin reduced hypoxia-ischemia induced modifications of the cortical metabolism and altered white matter microstructure as revealed in lactoferrin-supplemented rats.…”
Section: Discussionmentioning
confidence: 99%